PENGARUH CITRA MEREK (BRAND IMAGE) DAN KUALITAS WEBSITE (WEBSITE QUALITY) TERHADAP KEPUTUSAN PEMBELIAN (PURCHASE DECISION) MELALUI KEPERCAYAAN (E-TRUST) SEBAGAI VARIABEL INTERVENING (STUDI PADA KONSUMEN E-COMMERCE ZALORA.CO.ID DI KOTA SEMARANG) - Fadiah Adlina Putri Ghaisani; Dinalestari Purbawati (Universitas Diponegoro, 2020)
Competition in online business via e-commerce that more tight makes the e-commerce companies need to increase consumer decisions to buy products, in order to be able to survive and continue to get profit. This research was conducted with aim of examine Brand Image and Website Quality on the purchase decision through e-trust as an intervening variable. This research is quantitative study that uses explanatory research methods or explanative types. The sampling technique uses Purposive Sampling approach. Where the population is all Zalora.co.id consumers in Semarang City, while the sample is 100 Zalora.co.id consumers with certain criteria carried out. The technique of collecting data using questionnaires. The analysis used in this study is linear regression analysis using SPSS 21.0 for Windows software and mediation test (sobel test) to test the mediating effect of intervening variables. Based on the results of this research indicate that Brand Image and Website Quality has a partial and simultaneous effect on e-trust, which when they together with Website Quality it has the greatest influence on e-trust. In addition, Zalora.co.id also has to improve the quality of its website by making an attractive website appearance, increasing the confidence of website users to trust the information provided by the website, the effectiveness and suitability of information added on the website, security in providing personal data, and make it easier for websites to communicate with companies, Zalora.co.id, so this will increase trust, which in turn increases Zalora.co.id's consumer purchasing decisions.Keywords: Brand Image, Website Quality, E-Trust, and Purchasing Decisions.